Design and Implementation of a Low Cost DAQ System for Thermoelectric Property Measurements - Sumphao, T.; Thanachayanont, C.; Seetawan, T. (Procedia engineering, 2012)
The research proposed the design and implementation USB data acquisition system (DAQ) for measurement Seebeck coefficient. This system consists of microcontroller PIC18F4550 and high- resolution analog to digital converter (A/D) MCP3553, voltage reference LM4140 and the “Microchip USB Device Firmware Framework”. The PC software develops in Delphi visual programming. The system was used to measure bulk Ca3Co4O9 thermoelectric material and the performance was satisfied.